2012
DOI: 10.14411/eje.2012.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of host egg age on preference, development and arrestment of Telenomus remus (Hymenoptera: Scelionidae)

Abstract: Abstract. Age of host eggs can be a limiting factor for egg parasitoids. It is expected that old eggs are less preferred by egg parasitoids, which can discriminate between eggs of different ages by using chemical cues. The objective of this study was to determine the preference, development and arrestment of Telenomus remus Nixon (Hymenoptera: Scelionidae) parasitizing Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) eggs of different ages. This egg parasitoid preferred to parasitize 1-and 2-day-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Furthermore, different ages (1, 2 or 3 days old) of Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) eggs affect the percentage emergence of Telenomus remus Nixon (Hymenoptera: Scelionidae) (Peñaflor et al , 2012). We conclude that the effects of host age vary according to parasitoid species.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, different ages (1, 2 or 3 days old) of Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) eggs affect the percentage emergence of Telenomus remus Nixon (Hymenoptera: Scelionidae) (Peñaflor et al , 2012). We conclude that the effects of host age vary according to parasitoid species.…”
Section: Discussionmentioning
confidence: 99%
“…The parasitism rate of 1-d-old T. peregrinus eggs by C. noackae in the laboratory was higher than that reported on Eucalyptus grandis W. Hill ex Maiden (Myrtales: Myrtaceae) clone Tag 5 in South Africa, which was 34.1 and 16.6% in 0-to 1-d-old and 4-to 5-d-old eggs, respectively, of this host (Mutitu et al 2013). Hosts in the initial development stages may be more appropriate than those in the late stages for hymenopteran parasitoids (Lytle et al 2012;Peñaflor et al 2012;Tavares et al 2013) as shown for C. noackae (Mutitu et al 2013), Gonatocerus ashmeadi Girault, Gonatocerus triguttatus Girault, and Gonatocerus fasciatus Girault (Hymenoptera: Mymaridae) (Irvin & Hoddle 2005), Trichogramma species (Vianna et al 2009;Soares et al 2012), and Eulophidae species (Pereira et al 2008a,b).…”
Section: Resultsmentioning
confidence: 55%
“…Hosts in the initial development stages may be more appropriate than those in the late stages for hymenopteran parasitoids (Lytle et al 2012;Peñaflor et al 2012;Tavares et al 2013) as shown for C. noackae (Mutitu et al 2013), Gonatocerus ashmeadi Girault, Gonatocerus triguttatus Girault, and Gonatocerus fasciatus Girault (Hymenoptera: Mymaridae) (Irvin & Hoddle 2005), Trichogramma species (Vianna et al 2009;Soares et al 2012), and Eulophidae species (Pereira et al 2008a,b).…”
Section: Resultsmentioning
confidence: 99%